Development of a Digital Body Weight Scale Prototype with IoT-Based BMI Calculation and Real-Time Weight Tracking - Hasti, Lubna Nadra; Permata, Endi; Aribowo, Didik (Institut Teknologi Dirgantara Adisutjipto, 2025)
Obesity is a growing health concern in Indonesia, with its prevalence steadily increasing and contributing to a variety of non-communicable diseases such as diabetes and heart disease. One effective way to monitor and manage body weight is by regularly calculating the Body Mass Index (BMI). This study aims to develop a digital weighing scale prototype based on the Internet of Things (IoT), equipped with BMI calculation and real-time weight tracking features. The prototype utilizes load cell sensors, HX711, ESP8266, and an OLED display for measuring weight, which is then transmitted to a Flutter-based application (MyWeightApp) connected to Firebase for data storage and graphical visualization. The research adopts the waterfall model for system development, encompassing requirements analysis, planning, modeling, construction, and system handover. Hardware testing demonstrates an accuracy rate of 0.78% error, well below the 5% tolerance threshold. Software testing using black-box testing confirms that the application successfully tracks weight, calculates BMI, and provides effective weight progress graphs. The results of this study indicate that the IoT-based digital weighing scale prototype developed can serve as a practical solution for obesity prevention and health monitoring in Indonesia.